2021
DOI: 10.3390/agronomy11020394
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Cell Culture of Dioscorea deltoidea—A Renewable Source of Biomass and Furostanol Glycosides for Food and Pharmaceutical Industry

Abstract: Dioscorea deltoidea is a medicinal plant valued for its high content of steroidal glycosides (SG) – bioactive compounds with cardioprotective and immunomodulation actions, also used to treat reproductive system disorders. To overcome the limitations of natural resources of this species, a suspension cell culture of D. deltoidea was developed as a renewable and ecologically sustainable source of raw biomass and SG. Cell culture demonstrated stable and intensive growth in the laboratory (20 L) and industrial (63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Recently, Lagunin et al [32] suggested high antihypoxic activity of phytopreparations based on P. japonicus, D. deltoidea and T. terrestris cell cultures that, in the case of P. japonicus and T. terrestris, exceeded the effect of the reference drug Mexidol. In addition, the cell biomass of D. deltoidea showed low toxicity in rats when administered orally even at high doses, up to 5 g/kg animal body weight [25].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Lagunin et al [32] suggested high antihypoxic activity of phytopreparations based on P. japonicus, D. deltoidea and T. terrestris cell cultures that, in the case of P. japonicus and T. terrestris, exceeded the effect of the reference drug Mexidol. In addition, the cell biomass of D. deltoidea showed low toxicity in rats when administered orally even at high doses, up to 5 g/kg animal body weight [25].…”
Section: Introductionmentioning
confidence: 99%
“…Dioscorea deltoidea, Tribulus terrestris and Panax japonicus are medicinal plants that are known to exhibit a large spectrum of pharmacological activities; however, their natural resources are dwindling [23][24][25]. Suspension cell cultures with the ability to produce triterpene and steroidal glycosides have been developed in our laboratory as a sustainable source of biomass and bioactive ingredients of these species [26][27][28][29][30], and their biochemical profiles have been investigated by using various methods [21,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations